Enhancing Pronunciation Proficiency through then Implementation of Audio-Visual Method in Eleventh Grade Students at Sma Negeri 1 Dampal Selatan - Rahmatul Ummu Arifin; Nahdawati; Sitti Hawaena; Uswatun Hasanah; Maslinda (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This research aims to determine whether the implementation of audio visual method can enhance the pronunciation proficiency of eleventh-grade students at SMA Negeri 1 Dampal Selatan. The main issue faced by the students was the difficulty in distinguishing short vowels, long vowels, and consonants in English, which affected their confidence in speaking. Therefore, the researcher implemented the audio visual method to allow students to imitate correct pronunciation through exposure to native speaker videos and visual media. The method The method used this research was quantitative with a pre-experimental design. The subjects consisted of 30 students from class XI F6. Before the treatment, students were given a pre-test to assess their initial pronunciation ability. The treatment was conducted in six meetings using audio visual. Afterward, a post-test was administered to measure their improvement. The data were analyzed using a paired sample t-test through SPSS. The results showed a significant improvement in the average score from 30.92 to 71.95. The t-test value 21.106 was higher than the t-table value 1.699, indicating that the null hypothesis was rejected and the alternative hypothesis was accepted. Therefore, it can be concluded that the implementation of audio visual method significantly enhanced the pronunciation proficiency in eleventh-grade students at SMA Negeri 1 Dampal Selatan